The Spanish farm - Mottram, R.H.; Galsworthy, John (London : Chatto and Windus, 1930)
Bibliotheek Camille Huysmans
Dedicator: Mottram, R.H., dedicatee: Huysmans, Camille
Eerste deel van "The Spanish farm trilogy"
Engels
Meerdelige publicatie
Keywords: Wereldoorlog 1